The Impact of Time-Restricted Eating and Intermittent Fasting on Glycemia, Body Weight, and Overall Well-Being in Patients with Type 2 Diabetes – A Review of Studies - Stolarczyk, Szymon Przemysław; Romańczuk, Kuba Borys; Wójcik, Zofia Martyna; Omasta, Bartosz; Rybak, Daria; Czerska, Magdalena Agata; Pietrukaniec , Paulina Dorota; Krupa , Olga; Kamińska-Omasta, Katarzyna; Furtak , Kinga (Quality in Sport, 2025)
Introduction Intermittent fasting is becoming increasingly popular, particularly among individuals with obesity. One variation of this approach is time-restricted eating (TRE), which involves consuming meals only during a specific time window, typically lasting between eight to twelve hours each day. Aim Of The Study The objective of this article was to analyze studies conducted on both animal and human models. This analysis enabled a presentation of the benefits and potential risks associated with time-restricted eating in the context of type 2 diabetes. Materials and Methods In the study, scientific articles retrieved from the PubMed and Google Scholar databases were used, utilizing keywords such as "intermittent fasting and type 2 diabetes," "intermittent fasting and glycemia," "metabolic effects of fasting," and "intermittent fasting in animals,". Articles in languages other than English were excluded. Summary Various fasting types led to reduced HbA1c, weight loss, and improved well-being in experimental groups. Researchers emphasize the need for further trials involving larger groups and longer observation periods to objectively assess the long-term effects of TRE on T2D. Establishing these findings is essential to maximizing the benefits of fasting while minimizing the risk of hypoglycemia. If practiced cautiously under medical supervision, intermittent fasting could serve as an effective and safe method for managing type 2 diabetes. Adjusting medication, monitoring glucose, and staying hydrated are crucial to minimizing hypoglycemia risk.